Thermodynamic modeling of the Fe-Mg-Si system - Du Y.; Zhao J.R.; Zhang C.; Chen H.L.; Zhang L.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A thermo dynamic modeling for the Fe-Mg-Si system is conducted. All of the experimental phase diagram and thermodynamic data available from the literature are critically reviewed and assessed using thermo dynamic models for the Gibbs energies of individual phases. The thermodynamic parameters for ternary liquid as well as binary phases αFeSi, (high-temperature form of FeSi2) and FeSi showing noticeable solubilities for Mg are evaluated in the optimization. Comparisons between the calculated and measured phase diagrams show that the measured isothermal six-lions at 1600°, 1454°, 727° and 710°C, the observed regions of primary phases are satisfactorily accounted for by the thermodynamic description. The limited thermodynamic data concerning the activity of Mg in liquid at 1350°C are found to be inconsistent with the well established phase relations. The liquidus projection and reaction scheme for the entire Fe-Mg-Si system are also presented. .